The when and what of measuring ECE quality: Analysis of variation in the Classroom Assessment Scoring System (CLASS) across the ECE day - Thorpe, K; Rankin, P; Beatton, T; Houen, S; Sandi, M; Siraj, I; Staton, S (Elsevier, 2020)
Observational assessment has become an integral component of the quality improvement agenda in Early Care and Education (ECE) and has been significant in directing attention to quality of interactions within the ECE setting. Understanding the functioning of observational assessment is increasingly important as the stakes are high. Assessment outcomes influence programme funding. Assessment criteria direct educators to preference particular types of experiences for children, grounded in the assumptions that these criteria are those that best predict children's’ school readiness, ongoing achievements and wellbeing. We examine two contextual factors that might affect assessment functioning: (1) When – the timing of assessment in the ECE day and (2) What – the content and format of the activities observed. We provide the example of the Classroom Assessment Scoring System (CLASS), analysing 11,341 observations cycles undertaken in a representative sample of 2306 Australian pre-K (age 3–4 years) through Year 2 (age 7–8 years) classrooms. Our data show a generalised decline in instructional, organisational and emotional support across the ECE day (8am to 4pm) with recovery in emotional support at the end of the day. Within-classroom analyses demonstrate that whole group and small group formats and science, math, and social science content inflate, while meal times, physical activity, and transitions constrain CLASS scores. Separate analyses for pre-K classrooms showed similar patterns. We discuss the findings in terms of the purpose of assessment and suggest that particular times and events in the ECE day might serve as barometers of quality.